Unraveling In Vivo Brain Transport of Protein‐Coated Fluorescent Nanodiamonds. Issue 42 (29th August 2019) - Moscariello, Pierpaolo; Raabe, Marco; Liu, Weina; Bernhardt, Sandra; Qi, Haoyuan; Kaiser, Ute; Wu, Yuzhou; Weil, Tanja; Luhmann, Heiko J.; Hedrich, Jana
Abstract: Nanotheranostics, combining diagnostics and therapy, has the potential to revolutionize treatment of neurological disorders. But one of the major obstacles for treating central nervous system diseases is the blood–brain barrier (BBB) preventing systemic delivery of drugs and optical probes into the brain. To overcome these limitations, nanodiamonds (NDs) are investigated in this study as they are a powerful sensing and imaging platform for various biological applications and possess outstanding stable far‐red fluorescence, do not photobleach, and are highly biocompatible. Herein, fluorescent NDs encapsulated by a customized human serum albumin–based biopolymer (polyethylene glycol) coating (dcHSA‐PEG) are taken up by target brain cells. In vitro BBB models reveal transcytosis and an additional direct cell–cell transport via tunneling nanotubes. Systemic application of dcHSA‐NDs confirms their ability to cross the BBB in a mouse model. Tracking of dcHSA‐NDs is possible at the single cell level and reveals their uptake into neurons and astrocytes in vivo. This study shows for the first time systemic NDs brain delivery and suggests transport mechanisms across the BBB and direct cell–cell transport. Fluorescent NDs are envisioned as traceable transporters for in vivo brain imaging, sensing, and drug delivery. Abstract : The blood–brain barrier is the biggest hurdle to overcome for the treatment of neurological disorders. Here, protein‐coated nanodiamonds are delivered to the brain and taken up by neurovascular unit cells after intravenous injection. Thus, for the first time, nanodiamonds with their unique properties and a flexible protein coating for the attachment of therapeutics emerge as a potential platform for nanotheranostics of neurological disorders.